2016
DOI: 10.1158/1535-7163.mct-15-0675
|View full text |Cite|
|
Sign up to set email alerts
|

Dedifferentiation of Glioma Cells to Glioma Stem-like Cells By Therapeutic Stress-induced HIF Signaling in the Recurrent GBM Model

Abstract: Increasing evidence exposes a subpopulation of cancer cells, known as cancer stem cells (CSCs), to be critical for the progression of several human malignancies, including glioblastoma multiforme (GBM). CSCs are highly tumorigenic, capable of self-renewal, and resistant to conventional therapies, and thus considered to be one of the key contributors to disease recurrence. In order to elucidate the poorly understood evolutionary path of tumor recurrence and the role of CSCs in this process, we developed patient… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
101
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 105 publications
(104 citation statements)
references
References 54 publications
3
101
0
Order By: Relevance
“…Previous reporting demonstrated that Hypoxia-inducible factors (HIFs) are critical for maintenance of the BTIC niche and that HIF-1α (HIF1A) can directly modulate EZH2 expression via promoter binding 30,31 . We have shown that TMZ therapy increases the BTIC frequency in a HIF dependent manner 20,32 . Now we show that the TMZ-mediated increase in HIF1A is specific to the CD133+ BTIC compartment…”
Section: Ezh2 Expression Is Increased In the Btic Compartment During mentioning
confidence: 89%
See 1 more Smart Citation
“…Previous reporting demonstrated that Hypoxia-inducible factors (HIFs) are critical for maintenance of the BTIC niche and that HIF-1α (HIF1A) can directly modulate EZH2 expression via promoter binding 30,31 . We have shown that TMZ therapy increases the BTIC frequency in a HIF dependent manner 20,32 . Now we show that the TMZ-mediated increase in HIF1A is specific to the CD133+ BTIC compartment…”
Section: Ezh2 Expression Is Increased In the Btic Compartment During mentioning
confidence: 89%
“…The loss of stemness can be rescued by re-expressing ARL13B in KD cells ( Fig. 3B 32,37 . Immunoblot analysis indicated that when PDX lines cultured in NEB, the expression of ARL13B was significantly elevated in three different subtypes of GBM ( Fig.…”
Section: Arl13b Regulates Cellular Plasticity and Contributes To Tumomentioning
confidence: 97%
“…The human glioma U87MG (CVCL_0022) and U251 (CVCL_0021) cell lines were purchased from the American Type Culture Collection (Manassas, VA). The primary patient‐derived GBM1, GBM7 and GBM13 cells were prepared from specimens obtained at the N.N.…”
Section: Methodsmentioning
confidence: 99%
“…This alteration is an example of cellular plasticity, a mechanism by which GBM cells can transition from differentiated, treatment-sensitive states to treatment-resistant, undifferentiated GSC states. Hypoxia-induced factors (HIF) have been shown to participate in the regulation of the GSC niche(17, 50, 5355). This ability of HIF to influence cellular plasticity has been confirmed in breast cancer stem cells(56).…”
Section: Radiation Hypoxia and Cellular Plasticity: A Complex mentioning
confidence: 99%
“…We have previously shown that therapeutic stress induced by chemotherapy can activate cellular plasticity via HIF signaling under normoxic conditions(17). Several studies have recently confirmed that radiation also alters cellular plasticity.…”
Section: Radiation Hypoxia and Cellular Plasticity: A Complex mentioning
confidence: 99%